2016
DOI: 10.1007/s00520-016-3140-3
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based pre-habilitation is feasible and effective in radical cystectomy pathways—secondary results from a randomized controlled trial

Abstract: In patients awaiting RC, a short-term exercise-based pre-habilitation intervention is feasible and effective and should be considered in future survivorship strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 27 publications
5
63
0
Order By: Relevance
“…According to results of the review, prehabilitation appears to be acceptable to patients and feasible to implement with good levels of adherence supported by studies within the review [15,18,29]. This finding is further supported by the wider research literature [37]. Even an intensive prehabilitation exercise programme compared to home-based exercise was found to have good levels of adherence [38], as long as prehabilitation did not interfere with receipt of cancer treatment [12].…”
Section: Discussionmentioning
confidence: 65%
“…According to results of the review, prehabilitation appears to be acceptable to patients and feasible to implement with good levels of adherence supported by studies within the review [15,18,29]. This finding is further supported by the wider research literature [37]. Even an intensive prehabilitation exercise programme compared to home-based exercise was found to have good levels of adherence [38], as long as prehabilitation did not interfere with receipt of cancer treatment [12].…”
Section: Discussionmentioning
confidence: 65%
“…Although less objective measures of functional fitness (e.g. improved 6-min walk test (6-MWT) and increased muscle leg power) have been shown to improve within a 31-day timeframe in patients with cancer [35,36], it has previously proved difficult to improve VO AT, (as measured by CPET) by the MCID (1.5-2.0 ml/kg/min) for all comers in major benign [37] and malignant intra-abdominal surgery [11,31,38] using supervised exercise regimes. In addition, until recently, prehabilitation studies in urological patients have largely been aimed at reducing specific urological complications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Jensen et al [20] showed that a 2-week home-based program of pre-operative muscle strengthening exercises and endurance training was feasible and resulted in improvements in muscle power in bladder cancer patients prior to RC. However, because of the short time-window between decision for surgery and RC, there is a need to optimise the exercise stimulus for cardiopulmonary adaptations and the potential advantages of vigorous intensity interval exercise in this respect, were recently highlighted [21].…”
Section: Introductionmentioning
confidence: 99%